Desertification, migration, and herder-farmer conflicts in Nigeria: rethinking the ungoverned spaces thesis. (17th November 2021) - Lenshie, Nsemba Edward; Okengwu, Kelechi; Ogbonna, Confidence N.; Ezeibe, Christian
ABSTRACT: While previous studies have focused on how political and economic factors fuel herder-farmer conflicts, there is a dearth of knowledge on how desertification-induced migration amidst ungoverned spaces affect herder-farmer conflicts in Nigeria. Using data from qualitative dominant mixed method, this study interrogates how desertification-induced migration and state failure to provide security governance affect herder-farmer conflicts in Nigeria. It argued that poor security governance escalates the southward migration of herders and contributes to the intensification of herder-farmer conflicts in Nigeria. These conflicts endanger livelihoods, fuel population displacements, and undermine human security. The study concludes that effective security governance amidst increased desertification in Northern Nigeria presents an opportunity for regulating southward migration of herders, mitigating herder-farmer conflicts, and promoting human security in Nigeria.